Upaya Mahasiswa Stain Madina Dalam Penerapan Model Pembelajaran Radec (Read - Answer – Disscuss - Explain - And Create) Terhadap Peningkatan Kemampuan Berfikir Kritis Siswa Man 3 Mandailing Natal - Dedi Saputra Tinanbunan; Zulhajjah Zulhajjah; Ainun Mufidah; Puja Rahayu (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Critical thinking is one of the 21st century skills that students need to master in order to be able to face various personal and social problems in their lives. Critical thinking skills can be improved through the RADEC learning model. This research aims to determine the application of the RADEC learning model to improving students' critical thinking abilities. The method used was a pre-experiment with a one-group pretest-posttest design. The research was conducted on class X students at MAN 3 MADINA, Siabu District, Mandailing Natal Regency.The sample used in the research was 125 students. The instruments used were critical thinking ability tests and observation sheets. The critical thinking ability test is carried out in two stages, namely the pretest and posttest stages. From the research, it was found that the average score for students' critical thinking skills in the pretest was 74, while the average score for the posttest was 86. This means that there was an increase in students' critical thinking skills before and after treatment using the RADEC learning model.